2017
DOI: 10.3233/cbm-160546
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of MYCN gene amplification and protein expression in primary brain tumors: Astrocytoma and meningioma

Abstract: Our results challenge the concept of the neural specificity of MYCN by demonstrating contribution of MYCN in meningioma. Moreover, this study highlights the importance of research at both level of DNA and protein, to determine the biological functions and medical impacts of MYCN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…As the receptor subtype of angiotensin II, AGTR2 is expressed in sensory neurons and could be a potential target for nociception and neuronal regeneration [17]. MYCN, a member of MYC proto-oncogenes, expression levels may have a positive relationship with disease-free survival in astrocytoma and meningioma [18]. Also, potassium voltage-gated channel subfamily J member 8 (KCNJ8) may help to regulate blood pressure with the help of ABCC9 [19].…”
Section: Discussionmentioning
confidence: 99%
“…As the receptor subtype of angiotensin II, AGTR2 is expressed in sensory neurons and could be a potential target for nociception and neuronal regeneration [17]. MYCN, a member of MYC proto-oncogenes, expression levels may have a positive relationship with disease-free survival in astrocytoma and meningioma [18]. Also, potassium voltage-gated channel subfamily J member 8 (KCNJ8) may help to regulate blood pressure with the help of ABCC9 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study by Liu et al found that MYCN was involved in the malignant characteristics of erythroleukemia by inhibiting the activation of p21 . What's more, amplified MYCN gene was observed in rhabdomyosarcoma, pediatric T‐cell acute lymphoblastic leukemia, astrocytoma, and meningioma …”
Section: Discussionmentioning
confidence: 99%
“…As an example, correlation between gene amplification at global level by qualitative polymerase chain reaction (qPCR) and expression by IF is reported to be a challenging item, and we found it inconsistent in brain tumors. 17 This finding has a key impact on the therapeutic approach, so it’s worth to emphasize on an EGF/VEGF chimer characterized with an adequate amount of antibodies in contradiction of the EGF and VEGF function which aimed to prevent angiogenic and growth of breast tumor in mouse model. 18…”
Section: Discussionmentioning
confidence: 99%